Nonproton Ligand Sensing Domain Is Required for Paradoxical Stimulation of Acid-sensing Ion Channel 3 (ASIC3) Channels by Amiloride - Li, Wei-Guang (American Society for Biochemistry and Molecular Biology, 2011)
Acid-sensing ion channels (ASICs), which belong to the epithelial sodium channel/degenerin family, are activated by extracellular protons and are inhibited by amiloride (AMI), an important pharmacological tool for studying all known members of epithelial sodium channel/degenerin. In this study, we reported that AMI paradoxically opened homomeric ASIC3 and heteromeric ASIC3 plus ASIC1b channels at neutral pH and synergistically enhanced channel activation induced by mild acidosis (pH 7.2 to 6.8). The characteristic profile of AMI stimulation of ASIC3 channels was reminiscent of the channel activation by the newly identified nonproton ligand, 2-guanidine-4-methylquinazoline. Using site-directed mutagenesis, we showed that ASIC3 activation by AMI, but not its inhibitory effect, was dependent on the integrity of the nonproton ligand sensing domain in ASIC3 channels. Moreover, the structure-activity relationship study demonstrated the differential requirement of the 5-amino group in AMI for the stimulation or inhibition effect, strengthening the different interactions within ASIC3 channels that confer the paradoxical actions of AMI. Furthermore, using covalent modification analyses, we provided strong evidence supporting the nonproton ligand sensing domain is required for the stimulation of ASIC3 channels by AMI. Finally, we showed that AMI causes pain-related behaviors in an ASIC3-dependent manner. These data reinforce the idea that ASICs can sense nonproton ligands in addition to protons. The results also indicate caution in the use of AMI for studying ASIC physiology and in the development of AMI-derived ASIC inhibitors for treating pain syndromes.